Vehicle Number Plate Recognition System to Identify the Authenticated Owner of Vehicles - R. , Lalitha; B. , Sree Lekha; G. , Guhaspuran; P. , Krishnan; R. , Abishek (International Journal of Psychosocial Rehabilitation, 2020)
Automatic Number Plate Recognition (ANPR) is the primary source of the Vehicle Number Plate Recognition System. The number plate recognition system is a security system that plays a significant role in identifying the owner of a vehicle. In case of suspicion, the traffic policemen verify the license copy and other documents related to the vehicle. As it is time-consuming and difficult, the Number Plate Recognition system is suggested in this paper. The images of the number plates of the vehicles are scanned and stored in a repository in the system along with the information of the owner. When a suspected vehicle is scanned by the policemen, it generates a one-time password for the owner of the vehicle. Once it is processed, the information about the vehicle and the owner will be displayed. Thus, it helps to identify whether the vehicle is used by the authenticated user and thus helps to find the vehicles that are stolen. The ML Kit algorithm is used for the implementation process.